Turkey Entering the European Union Through the Balkan Doors: in the Style of a Great Power? - Bedrudin Brljavac (Romanian Journal of European Affairs, 2011)
Confronting an increasing EU opposition from a number of influential member states to its membership the AKP government adopted a multilateral approach to its foreign policy making resulting in dynamic economic and diplomatic policies with the countries from Asia, Africa, Latin America, and the Balkans region. In this article we analyzed the effects and consequences of a paradigmatic shift in Turkish foreign policy in the Western Balkans in relation to the country’s EU membership prospects. Through its pro-active economic and diplomatic initiatives in the region Turkey has been proving itself as indispensable country for the European Union membership. Thus, if the Turkish government concentrates more on solving its internal problems and continues its pro-active diplomacy in Western Balkans, among other regions, it could become not only a regional but also a global power.